Bioengineering the Cardiac Conduction System: Advances in Cellular, Gene, and Tissue Engineering for Heart Rhythm Regeneration - Naumova, Nataliia; Iop, Laura (Frontiers in Bioengineering and Biotechnology, 2021)
Heart rhythm disturbances originate as a result of different etiologies and may affect pediatric and adult patients with life-threatening consequences. When pharmacological therapy is ineffective in treating them, the unique clinical management option is the implantation of electronic devices to control and/or restore normal heart pacing. Although these artificial devices are life-saving, they display many limitations; not least, they do not have any capability to adapt to somatic growth or respond to neuroautonomic physiological changes. A biological pacemaker could offer a new clinical solution for restoring heart rhythm in cardiac conduction system disorder conditions. Several experimental approaches for the generation of biological pacemakers are currently established and widely studied, including cell-based, genes-based approaches and their combination. Pacemaker bioengineering is also emerging as a technology to regenerate nodal tissues. This review analyzes and summarizes the strategies applied so far for the development of biological pacemakers, and discusses current translational challenges towards the first-in-human clinical application.